Formulasi Coklat Batangan (Dark Chocolate) Dengan Ekstrak Kayu Manis Untuk Regulasi Gula Darah - Eliati; Sri Handayani; Rohani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to design a dark chocolate bar formulation with the addition of cinnamon extract as a functional food for blood sugar regulation. The research methods include formulations with varying concentrations of cinnamon extract (1%, 3%, 5%), organoleptic tests, bioactive content analysis (total phenols and flavonoids), and effectiveness tests on blood glucose levels in alloxan-induced hyperglycemic rats. The results showed that the formulation with 4% cinnamon extract had the best balance between sensory characteristics and effectiveness in reducing blood glucose levels (p<0.05). The combination of dark chocolate and cinnamon has the potential to be developed as an alternative functional food for people with type 2 diabetes mellitus. The conclusion of this study is that the formulation with 3% cinnamon extract is the most preferred sensory and has the potential to provide benefits in blood sugar regulation through the content of bioactive compounds such as cinnamaldehyde and procyanidin. This product has the potential to be developed as a functional food innovation that supports the prevention and management of type 2 diabetes mellitus, especially in community nursing practice. Keywords: Blood Sugar Regulation, Cinnamon, Dark Chocolate, Diabetes Mellitus, Functional Food.